PERILAKU JOB CRAFTING PEGAWAI DALAM MENINGKATKAN PELAYANAN PUBLIK DI KECAMATAN - Syamsul Alam; La Ode Mustafa; Gunawan; La Ode Muhammmad Elwan (Halu Oleo University, 2024)
The important role of employees in interactions between government and society in sub-districts attracts attention, especially regarding discretionary behavior such as job crafting which is considered to improve public services. The aim of this research is to determine the proportion of employees in the sub-district who are actively involved in job crafting behavior in improving public services, and to identify variations in the level of involvement among employees in the three dimensions of job crafting. This research used quantitative methods and involved all 39 employees from a sub-district government in Kendari City. Data was obtained through the use of a questionnaire with a Likert scale and distributed directly manually, and then analyzed using descriptive statistical analysis methods. The data analysis technique used was descriptive statistical analysis. The research results show that the majority of employees in this sub-district are active in job crafting, achieving around 75.9% ideal scores. However, variations in the level of involvement are seen among the dimensions of job crafting, namely seeking resources, seeking challenges, and reducing demands on the job. With a high standard deviation, it shows significant variation in the level of job crafting.